Talking back : senior scholars and their colleagues deliberate the past, present, and future of writing studies - Elliot, Norbert; Horning, Alice S. (Utah State University Press, 2020)
""Prestigious writing studies scholars deliberate on intellectual traditions, current practices, and directions for the future. Mid-career scholars react to each chapter with a thoughtful and measured response. Authors have three common experiences: responsibility for advancing a profession, research dedicated to advancing opportunities, and a sense of humility"--Provided by publisher"--